2013
DOI: 10.1097/iae.0b013e31826f0675
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Acute Endophthalmitis After Intravitreal Bevacizumab Injection in a Single Clinical Center

Abstract: A low risk of endophthalmitis consistent with the range of previous studies was observed notwithstanding the usage of multiple use of a single vial. Postinjection antibiotic drops may not be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 28 publications
0
43
0
1
Order By: Relevance
“…[10][11][12][13][14][15][16] The rate of endophthalmitis seems to be the same among different anti-VEGF agents, 12 different injection settings, 15 and different geographical locations. 17 Recent studies reported that endophthalmitis caused by Streptococcus species was significantly more frequent after intravitreal injection than after intraocular surgery. 10 Considering the fact that Streptococcus species comprise at least 41% culturable adult salivary flora, the difference in causative organisms in these two settings has been attributed to the contamination of injection field by aerosolization or droplet spread.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16] The rate of endophthalmitis seems to be the same among different anti-VEGF agents, 12 different injection settings, 15 and different geographical locations. 17 Recent studies reported that endophthalmitis caused by Streptococcus species was significantly more frequent after intravitreal injection than after intraocular surgery. 10 Considering the fact that Streptococcus species comprise at least 41% culturable adult salivary flora, the difference in causative organisms in these two settings has been attributed to the contamination of injection field by aerosolization or droplet spread.…”
Section: Methodsmentioning
confidence: 99%
“…Although most of the US retina specialists prefer to use post-injection topical antibiotics, recent studies report a significant increase in the antibiotic resistance of the isolated specimens from ocular flora and a greater rate of endophthalmitis with the use of topical antibiotics. 17,23,24 Considering the often devastating outcome of endophthalmitis after intravitreal injections, and the importance of immediate treatment, the surgeons should instruct all patients to return at the first sign of any visual disturbance, or ocular pain.…”
Section: Methodsmentioning
confidence: 99%
“…In einer retrospektiven 6-Jahres-Analyse berichtet Moshfeghi et al von 12 Patienten mit einer Endophthalmitis von 60 322 behandelten Augen, was einer Inzidenz von 0,02 % entspricht [17]. Eine irische Studie berichtet von einer Inzidenz von 0,1 % bei 5900 Injektionen und eine japanische Arbeit berichtet von einer Inzidenz von 0,095 % bei 5236 behandelten Augen [18,19].…”
unclassified
“…As many patients have active disease in both eyes, ophthalmologists increasingly face the dilemma of timing and balancing risks and benefits of bilateral treatments. Bilateral same-day intravitreal injections improve cost-effectiveness and are more convenient for the patient; however, many physicians are hesitant to treat both eyes on the same day for fear of bilateral endophthalmitis and vision loss [1,2]. A 2010 survey revealed that only 46% of retina specialists in the US were performing bilateral simultaneous intravitreal injections [3].…”
mentioning
confidence: 99%
“…Two publications from the Middle East reported bilateral endophthalmitis after bilateral intravitreal bevacizumab injections. One publication reported two patients with bilateral Staphylococcus epidermidis endophthalmitis [1], and the other listed one patient with bilateral culture-negative endophthalmitis [2].…”
mentioning
confidence: 99%